FERTILITAS DAN DAYA TETAS TELUR PUYUH (Coturnix coturnix japonica) PADA BERBEDA SEX RATIO - Budi Indarsih; MH Tamzil; H Anam (Universitas Djuanda, 2026)
This study was conducted to determine the fertility and hatchability of Japanese quails (Coturnix coturnix japonica) eggs at different sex ratios. Using a completely randomized design, a total of 246 female and 57 male quail were placed in colony cages which were divided based on sex ratios of 1:3 (R1), 1:4 (R2), 1:5 (R2) and 1:6 (R4) with 3 replicates per treatment. Quails were offered a commercial quail feed with 18-21% crude protein and metabolizable energy of 2,800 kcal/kg. A total of 540 fertile eggs for three hatching batches, per batch using 135 eggs were imposed. Sex ratios affected fertility and hatchability, and intermediate embryo mortality (P<0.05). Fertility was the highest in R2 (94.9%) and the lowest in R4 (74.1%). The hatchability of eggs was highest at R1 (82.4%) and lowest at R4 (63.2%). Middle embryo mortality was the highest at R4 (12.9 %) and the lowest at R2 (1.5%). A sex ratio of 1:3 or 1:4 produces the best fertility and hatchability in Japanese quail breeding